1977
DOI: 10.1073/pnas.74.9.3681
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to estrogen receptor: Immunochemical similarity of estrophilin from various mammalian species

Abstract: Immunoglobulin obtained from the serum of rabbits immunized with a highly purified preparation of estradiol-receptor complex from calf uterine nuclei has been shown to contain specific antibodies to the receptor protein (estrophilin) The action of estrogenic hormones in stimulating growth and function of female reproductive tissues takes place primarily, though perhaps not exclusively, through their interaction with an extranuclear receptor protein (estrophilin) present in characteristic amounts in hormone-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
2

Year Published

1980
1980
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(52 citation statements)
references
References 17 publications
2
47
1
2
Order By: Relevance
“…Similar observations were made with antibodies against the rabbit uterine progesterone receptor [7]. These results contrast with the limited shift to the 10-14-S region induced by antibodies against calf uterine oestrogen receptor [4]. An attempt to quantitate the heavy immunoglobulin-receptor complexes showed that they increased with IgG-G concentration, reached a plateau and then decreased.…”
Section: Discussioncontrasting
confidence: 41%
“…Similar observations were made with antibodies against the rabbit uterine progesterone receptor [7]. These results contrast with the limited shift to the 10-14-S region induced by antibodies against calf uterine oestrogen receptor [4]. An attempt to quantitate the heavy immunoglobulin-receptor complexes showed that they increased with IgG-G concentration, reached a plateau and then decreased.…”
Section: Discussioncontrasting
confidence: 41%
“…Sucrose gradient sedimentation with [ 3 H]estradiol as ligand confirmed the presence of ER␣ in the 2-week-old mouse VP. In this system, ER␤ sediments in the 4 S region (fractions 11-20), whereas ER␣ sediments as an 8 S peak (fractions 1-10) (16). A specific 8S [ 3 H]estradiol binding peak was present in extracts from 2-week-old VP as well as from adult uterus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sedimentation studies were carried out as described in ref. 16. Cytosols were incubated for 3 h at 0°C with 10 nM [ 3 H]estradiol-17␤ (Amersham Pharmacia) in the presence or absence of 50-fold excess of cold estradiol, and the unbound steroid was removed with dextran-coated charcoal.…”
Section: Preparation Of Cytosol For Sucrose Density Gradient Centrifumentioning
confidence: 99%
“…The sucrose gradient centrifugation experiments show that, in low-salt sucrose gradients, the native ER␤ present in cytosol from rat mammary glands sediments in the 4S region whereas ER␣ sediments as an 8S peak as expected (22). This has been observed in several tissues (prostate, lung, uterus) in which ER␣ and ER␤ are present (unpublished data).…”
Section: Discussionmentioning
confidence: 71%
“…Sedimentation studies were carried out as described previously (22). Breast tissue cytosols were incubated for 3 h at 0°C with 10 nM [ 3 H]estradiol-17␤ (Amersham) in the presence or absence of 50-fold excess of cold estradiol, and the unbound steroid was removed with dextrancoated charcoal.…”
Section: Preparation Of Cytosol For Sucrose Density Gradient Centrifumentioning
confidence: 99%